Buckling and shape control of prestressable trusses using optimum number of actuators - Manguri, Ahmed; Saeed, Najmadeen; Szczepanski, Marcin; Jankowski, Robert (Scientific reports, 2023)
This paper describes a method to control the nodal displacement of prestressable truss structures within the desired domains. At the same time, the stress in all members is unleashed to take any value between the allowable tensile stress and critical buckling stress. The shape and stresses are controlled by actuating the most active members. The technique considers the members’ initial crookedness, residual stresses, and slenderness ratio (S). Furthermore, the method is premeditated so that the members with an S between 200 and 300 can carry only tension before and after adjustment (i.e., the maximum compressive stress for the members with an S between 200 and 300 is zero). In addition, the derived equations are coupled with an optimization function that relies on five optimization algorithms (interior-point, trust-region-reflective, Sequential quadratic programming (SQP), SQP-legacy, and active-set). The algorithms identify and then exclude inactive actuators in the subsequent iterations. The technique is applied to several examples, and its results are compared with a quoted method in the literature.